El ara romana de Suatorre de Ambía (Orense) y sus inscripciones - Rivas Fernández, Juan Carlos; Rivas Quintas, Eligio (Antigüedad y Cristianismo, 1990)
In this article the authors studiy a Roman ara later christianised which was found in Suatorre de Ambia (San Esteban de Ambia, Baños de Molgas, Orense) whose primitve inscription was erased in the Eriy Middle Ages. In this epigraphical space, and on both sides of the ara was engraved a doule text of deposition of relics and in which is mentioned a certain person, Analous, who was probably one of the unknown bishops of the Auriense diócesis. As in many other such cases which exist in Galicia, its ancient focus was enlarged, squared and deepened to serve as a receptacle for the Christian relics. The hypothesis utilized is that at least one of the texts embossed in relief can be dated between the first years of the eleventh century and the beginning of the last third of the century. This is deduced from the fact that only one kilometer away is located the pre-Romanic chapel of Santa Eufemia de Ambia where fragments of an inscription of the Mozarabic period, with a similar type of letter and technique, were found. The final conclusion, that this may be an ara which supported one of the lateral altars in the afore mentioned pre-Romanic chapel, is based on the fact that there exists a primitive triple advocation to the Saviour, Saint Mary and Saint Eufemia equal to one that still can be observed on the central altar which is supported by a Roman ara with an inscription dedicated to the Water Nymphs.